OPTIMALISASI POWER POINT SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF UNTUK GURU DALAM KEGIATAN BELAJAR MENGAJAR - Suyono Suyono; Suhari Suhari; Dwi Retnani Srinarwati; Nur Sabilatul Ulfa; Natasha Bilqies Andriayani (Jurnal Abdimas Bina Bangsa, 2022)
The purpose of this service activity is to provide training on the development of power point learning media as interactive learning for teachers of SMA Muhammadiyah 1 Taman Kecamatan Taman, Sidoarjo Regency. The service method used includes lectures, questions and answers, discussions and practice. The steps for the Community Service program are 1) Compile and develop training materials, 2) Training Phase, 3) Practice stage for assisting the creation of interactive media in the form of power points. Community service has been carried out showing that the training that has been carried out in activities can improve the ability of Muhammadiyah 1 Taman SMA teachers for the development of knowledge and analysis and creativity in making power points as interactive media as learning media in SMA